Elasto-hydrodynamic lubrication of the journal bearing system with a relief groove in the scroll compressor: Simulation and experiment. (January 2022) - Wang, Che; Wu, Jianhua; Cheng, Junming; Zhang, Shuai; Zhang, Kang
Abstract: A scroll-type compressor that operates at a lower frequency has higher requirements for the reliability of the journal bearing system. A relief groove on the bearing frame can improve the lubricating condition by its deformation. In this study, a coupled model of the rotor, bearing, and bearing frame was developed. An experiment was also conducted to measure the displacement of the journal center, and the results showed good consistency with the numerical simulation. It is illustrated that the minimum film thickness increases significantly and the maximum oil film pressure decreases when a circumferential relief groove is used in the bearing frame according to the simulation results. In addition, the endurance test also showed that severe wear could be avoided in this case. Highlights: A coupled model of the rotor, bearing, bearing frame is developed. The displacement response of journal center is simulated and measured. Relief groove on bearing frame significantly improves lubricating condition.